DIALOG IMAJINER ANTARA ZINDA RUD (MUHAMMAD IQBAL) DENGAN AL HALLAJ DALAM KARYA JAVID NAMA - Muzairi Muzairi (UIN Sunan Kalijaga Yogyakarta, 2015)
Muhammad Iqbal’s Javid Nama follows Ibn Arabi, Marri and Dante. Iqbal depictshimself as Zind Rud (a stream, full of life) guided by Rumi the master, throughvarious heavens and spheres and has the honour of approaching Divinity and comingin contact with divine illuminations. Several problems of life are discussed and answersare provided. It is an exceedingly enlivening study. Iqbal stated that Hallaj has innerreligious involvement and becomes one of few people having Divine experience.